Actualities on molecular pathogenesis and repairing processes of cerebral damage in perinatal hypoxic-ischemic encephalopathy - Praticò Andrea D; Distefano Giuseppe (BMC, 2010)
Abstract Hypoxic-ischemic encephalopathy (HIE) is the most important cause of cerebral damage and long-term neurological sequelae in the perinatal period both in term and preterm infant. Hypoxic-ischemic (H-I) injuries develop in two phases: the ischemic phase, dominated by necrotic processes, and the reperfusion phase, dominated by apoptotic processes extending beyond ischemic areas. Due to selective ischemic vulnerability, cerebral damage affects gray matter in term newborns and white matter in preterm newborns with the typical neuropathological aspects of laminar cortical necrosis in the former and periventricular leukomalacia in the latter. This article summarises the principal physiopathological and biochemical processes leading to necrosis and/or apoptosis of neuronal and glial cells and reports recent insights into some endogenous and exogenous cellular and molecular mechanisms aimed at repairing H-I cerebral damage.